Reactive power control in micro-grid networks using adaptive control - Moghayadniya, A.; Razavi, E. (Національний технічний університет "Харківський політехнічний інститут", 2019)
Purpose. Despite their economic and environmental benefits, distributed products in power systems have caused problems in power systems. One of the most important issues in this regard is voltage fluctuations and frequencies in Micro-grids, which depends on several factors, such as variable consumption load and errors in powersystems. One of the main challenges associated with the use of Micro-grids is power management among distributed generation sources. Power management plays a pivotal role in numerous Micro-grids and may ensure the stable and improved performance of Micro-grids in the permanent status of the system. The present study aimed to examine the power control in Micro-grids by proposing an adaptive control method along with the PID controller for power management and coordination in Micro-grids. This coordination system operates between production sources and controlling the voltage and frequency levels against the possible disturbances occurring anywhere in the system loop. The results of the simulation of the proposed algorithm in MATLAB software environment exhibited a high success rate (i.e., proper response to the fluctuations in the Micro-grid) and extremely low error rate (i.e., proper reactive power in the grid).

Цель. Несмотря на их экономические и экологические преимущества, распределенные продукты в энергосистемах приводят к возникновению проблем в последних. Одним из наиболее важных вопросов в этой связи являются колебания напряжения и частоты в микросетях, которые зависят от нескольких факторов, таких как переменная нагрузка потребления и ошибки в энергосистемах. Одной из основных проблем, связанных с использованием микросетей, является энерго-менеджмент источников распределенной генерации. Энерго-менеджмент играет ключевую роль во многих микросетях и может обеспечить стабильную и улучшенную работу микросетей при постоянном состоянии системы. Настоящее исследование направлено на исследование энерго-менеджмента в микросетях путем предложения адаптивного метода управления вместе с ПИД-контроллером для энерго-менеджмента и координации в микросетях. Эта система координации функционирует между источниками производимой энергии и контролирует уровни напряжения и частоты в отношении возможных помех, возникающих в любом месте контура системы. Результаты моделирования предложенного алгоритма в программной среде MATLAB показали высокую степень успеха(то есть правильную реакцию на колебания в микросети) и чрезвычайно низкую частоту ошибок(то есть надлежащую реактивную мощность в сети).
Keywords: control parameters; online parameter setting; proportional-integral-derivative controller (PID); параметры управления; онлайн настройка параметров; пропорционально-интегрально-дифференцирующий (ПИД) контроллер